2019
DOI: 10.21037/jtd.2018.12.118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of volume reduction in giant left atrium during surgical ablation of atrial fibrillation

Abstract: Background: An enlarged left atrium (LA) is a well-known risk factor for ablation failure of atrial fibrillation (AF). We analyzed the result of concomitant AF ablation in patients with a giant LA and evaluated the effect of LA volume reduction.Methods: Between 2000 and 2011, 116 patients with a giant LA (antero-posterior dimension ≥70 mm) who underwent surgical AF ablation during MV surgery were retrospectively reviewed. Among these, 28 patients received aggressive LA volume reduction procedure (reduction gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…The principal indication for LA reduction surgery is the presence of compressive symptoms or a history of thromboembolic events. 8 , 15 , 17 , 21 , 24 , 25 As expected, most of our participants had this medical history at the preoperative stage, but we observed a significant reduction of these symptoms after surgery. Likewise, these results are linked to the substantial improvement in NYHA functional class observed during the follow-up, which is directly correlated to the patients' quality of life and mortality risk.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The principal indication for LA reduction surgery is the presence of compressive symptoms or a history of thromboembolic events. 8 , 15 , 17 , 21 , 24 , 25 As expected, most of our participants had this medical history at the preoperative stage, but we observed a significant reduction of these symptoms after surgery. Likewise, these results are linked to the substantial improvement in NYHA functional class observed during the follow-up, which is directly correlated to the patients' quality of life and mortality risk.…”
Section: Discussionsupporting
confidence: 78%
“…Certain authors argue that AF, a mortality predictor in patients with GLA, could be another indication for LA reduction surgery. 22 , 24 The dilatation of the LA is one of the predictors of the modified Maze procedure; in a cohort of patients undergoing operation for AF, Kawaguchi and colleagues 26 demonstrated that those remaining in AF (vs patients with restored SR) had a significantly higher incidence of GLA and larger cardiothoracic ratio and LA dimension; most patients with postoperative LA size less than 40 mm or cardiothoracic ratio less than 55% had restored SR. Kim and colleagues 25 found that LA volume reduction and cryoablation instead of radiofrequency were protective against AF recurrence during surgical ablation of AF. Kasemsarn and colleagues 27 reported that reducing the LA diameter to less than 50 mm increases the success of conversion to SR in patients undergoing radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LA reduction surgery is already an established procedure (30)(31)(32)(33)(34) primarily indicated alongside other surgical procedures to treat an enlarged LA or chronic atrial fibrillation in patients with mitral valve disease (31). Several studies have highlighted the benefits of LA reduction surgery in these circumstances, most commonly resulting in increased restoration and maintenance of sinus rhythm, with no significant increases in mortality or post-operative complications (35)(36)(37)(38)(39)(40)(41). The exact mechanism for these improvements is not clearly understood.…”
Section: The Potential Of Left Atrial Reduction Surgerymentioning
confidence: 99%
“…[ 16 ] MVR combined with LA volume reduction with cryoablation led to high rates of sustained relief from AF with incidences of 84.2%, 74.3% and 54.5%, at 1, 3 and 5 years respectively, compared to 49.0%, 33.2% and 28.4%, respectively in non-reduction group ( P = 0.013). [ 17 ]…”
Section: Introductionmentioning
confidence: 99%